Murabahah Financing in the Perspective of Islamic Law - Habibi (Maaliyah: Journal of Islamic Economic Law and Islamic Finance, 2025)
The development of the current era encourages financial institutions such as Islamic banking to continue to develop and produce their best products. One of them is a financing product with a murabaha contract. Murabahah financing. Murabahah is a sale and purchase agreement between two parties, where the buyer and seller agree on the selling price, which consists of the purchase price plus the cost of purchase and profit for the seller. Another understanding of murabahah is the sale and purchase of goods by stating the acquisition price and profit (margin) agreed upon by the seller and buyer. This research aims to identify sharia principles carried out by financial institutions such as Islamic banks on murabahah financing products. This research uses a qualitative descriptive approach with data sources derived from library research, namely collecting data by using written materials.